Analisis Penggunaan Sistem Informasi Manajemen Rumah Sakit di Rumah Sakit Umum Daerah Wonosari, Gunungkidul, Yogyakarta: Analysis of Using Management Information System (HIS) at Public Hospital Wonosari Regency, Gunung Kidul - Aula, Ahmad Samratul; Sulistyawati (International Journal of Healthcare Research, 2022)
Background:  Hospital Management Information System is a computer system that processes the entire flow of health services business processes, including reporting and administrative procedures to obtain information quickly, precisely, and accurately. Gunungkidul District Hospital is a type B hospital that has implemented SIMRS. The purpose of this research was to analyze SIMRS by using the Technology Acceptance Model (TAM) approach in Gunungkidul District Hospital. Methods: This type of research was quantitative research with a cross-sectional design. In this study, the samples were 79 people consisting of staff, nurses, and doctors recruited by accidental sampling technique. An questionnaire was used as an instrument to collect the data. The analysis was done using Univariate and Bivariate. Results: This study found a relationship between perceived ease of use with the use of SIMRS with a significant value of 0.030. Perception ease of use is the one variable that determining the use of SIMRS in Gunungkidul District Hospital.   Conclusion: The development of an information system that is friendly and easy to use by health workers will encourage the use of more effective and sustainable information systems in hospitals.